2008
DOI: 10.1007/s00787-008-1009-9
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating behaviour and attitudes, associated psychopathology and health-related quality of life: results of the BELLA study

Abstract: The high prevalence of disordered eating in the general population of Germany is of great concern. Health professionals should not only be aware of disordered eating in underweight adolescents, but in all youth, especially overweight individuals. Disordered eating behaviour is associated with a wide range of psychopathological and psychosocial concerns. Thus, youngsters engaging in disordered eating behaviour should also be explored for other serious mental or social problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
135
2
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(171 citation statements)
references
References 47 publications
21
135
2
13
Order By: Relevance
“…The findings confirm those of Herpertz-Dahlman et al (2008) who found the presence of any disordered eating in adolescents was negatively associated with health-related QOL. Our findings add a valuable longitudinal perspective and suggest that subclinical disordered eating has a lasting negative impact on mental-health-related QOL.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings confirm those of Herpertz-Dahlman et al (2008) who found the presence of any disordered eating in adolescents was negatively associated with health-related QOL. Our findings add a valuable longitudinal perspective and suggest that subclinical disordered eating has a lasting negative impact on mental-health-related QOL.…”
Section: Discussionsupporting
confidence: 89%
“…Such an investigation can inform us as to whether such behaviours are trivial, or whether the presence of any disordered eating behavior results in significant, long-term impairment of QOL. If this latter scenario is correct, then, given that a significant minority of the population is affected (Herpertz-Dahlman et al, 2008), this represents a major public health problem and suggests a need for community-wide prevention and education efforts.…”
mentioning
confidence: 99%
“…Thus, all latent variables were adequately operationalized (by their respective observed indicators) and their meaning does not vary by gender. 6 The 6 As the current manuscript includes the maximum permitted number of tables and figures, the correlations among the 10 latent variables and the 28 observed indicators and time-varying covariates stratified by gender are available on request from the corresponding author. standardized factor loadings for each gender are shown in Table 3.…”
Section: Examination Of Measurement Model and Factor Loading Invariancementioning
confidence: 99%
“…Sebagian besar responden yang memiliki persepsi tubuh negatif mengalami eating disorders. Hal ini sesuai dengan penelitian yang dilakukan oleh Herpertz-Dahlmann et al (24) yang menyatakan bahwa jika persepsi tubuh yang negatif tidak diperbaiki atau diterapi maka lama kelamaan akan mengalami eating disordes karena persepsi tubuh memiliki pengaruh yang besar terhadap eating disorders. Hal ini sesuai karena kriteria usia dan jumlah populasi yang diteliti oleh Herpertz-Dahlmann et al (25) tidak jauh berbeda dengan kriteria usia yang dilakukan oleh peneliti yaitu pada usia remaja sampai dewasa muda.…”
Section: Pembahasanunclassified